Policy Implementation of Increasing Investment As An Efforts To Reach The Target Of Local Revenues (PAD) In Autonomy Era (Study In Local Government of Pasuruan Regency) - Larasati, Tika (Jurnal Administrasi Publik, 2015)
Abstract: Implementasi Kebijakan Peningkatan Investasi Sebagai Upaya Peningkatan Pendapat Asli Daerah (PAD) Di Era Outonomy Daerah. Sejalan dengan kebijakan dan program pemerintah pusat, maka diharapkan pemerintah daerah dapat memajukan pembangunan, kemandirian dan kemajuan daerah pada sektor investasi. Hasil penelitian yaitu Pemerintah Kabupaten Pasuruan secara responsif menyadari potensi yang ada untuk dapat terus meningkatkan PAD sebagai modal untuk pembangunan daerah dengan upaya menarik dan mengundang para investor. Bentuk responsif yang dilakukan oleh pemerintah daerah yaitu dengan memformulasikan kebijakan peningkatan investasi, pelaksanaan dengan menerapkan pelayanan terpadu satu pintu, menyelenggarakan pameran promosi investasi, menyelenggarakan business gathering. Dalam Pelaksanaannya terdapat faktor penghambat seperti faktor yuridis, faktor RTRW, dan faktor administrasi. Selain itu terdapat faktor pendukung seperti potensi daerah, keadaan infrastruktur dan fasilitas, iklim sosial dan politik yang kondusif, serta penghargaan investment award yang diberikan dari pemerintah pusat melalui BKPM. Dampak lainnya yaitu peningkatan penyerapan tenaga kerja, pendapatan masyarakat dan UMKM. Selain itu terdapat dampak negatif yaitu kerusakan jalan yang diakibabkan kegiatan-kegiatan produksi dengan melibatkan kendaraan bertonase besar. Jika tidak ada penanganan lebih lanjut akan menghambat mobilitas ekonomi dikarenakan akses jalan merupakan faktor penting dalam pertumbuhan nilai investasi. Kata Kunci: kebijakan, implementasi, Pemerintah Daerah, investasi, PAD Abstract: Policy Implementation of Increasing Investment As An Efforts To Reach The Target of Local Revenues (PAD) In Autonomy Era (Study in Local Government of Pasuruan Regency). In line with the policy and program of central government, so it’s expected of local government can promote development, independence and progress of the region in the investment sector. The research results is local government of Pasuruan Regency responsively realize the potential that exist to be able to continues to increase local revenue  as a capital for regional development with efforts to attract and invite the investor come to Pasuruan. The responsive forms that made by local government of Pasuruan Regency are formulating policy of increasing investment with implementing of one-stop service delivery, organized an exhibition of investment promotion and organizing business gathering. During the implementation there are inhibiting factors such as the judicial factors, spatial factors and administrative factors. Besides that there are supporting factors such as regional potential, infrastructure condition, facilities and basic facilities, the conducive of social and political climate also the achievement of investment award that come from central government through BKPM. The others impacts that occur is increased the absorption employment, community income and UMKM. In addition, there are a negative impact which is the road damage that caused the production activities involving large tonnage vehicles. If there are no further treatment and attention it will hamper the economic mobility because the access road is an important infrastructure factors in investment growth.   Keyword: policy,  implementation, local government, investment, local revenues